Metode Pembelajaran Masa Kekhalifahan Abbasiyah - Dhaiman, Arif Noor; Hidayat, Tatang; Istianah, Istianah (Civilization Research: Journal of Islamic Studies, 2023)
The purpose of this study is to find out the learning methods of the Abbasid Caliphate. The research method used is qualitative with a literacy study approach. The results show that the 'ilmiyyah learning method is directed to form a level or type of deep thinking, but it is not allowed to release the spirit of the teaching-learning process in the theme of creation, khashiyyah (characteristics of objects and potential for life), and utilization according to shara' law "axiological aspects". Regarding the techniques, it is obligatory to increase the atmosphere of thinking and linking with facts, such as hands-on practices and laboratory experiments. The format of education during the Abbasid Caliphate, whether formal (madrasas, Sufi dormitories), non-formal (halqahs in mosques or shaikhs' houses), or informal (home education) was part of the technique, so it was dynamic according to the situation and conditions surrounding it.